A history of children's books in 100 books - Cave, Roderick; Ayad, Sara (Richmond Hill, Ontario : Firefly Books Ltd. ; Buffalo, New York : Firefly Books (U.S.) Inc., 2017)
While the modern children's book, intended specifically for the enjoyment of children, did not emerge until 18th-century Europe, its roots span centuries and continents: children's literature began with fables, myths and folk tales from the oral tradition. A History of the Children's Book in 100 Books takes a global perspective and traces the development of the genre from ancient stories such as Aesop's Fables and the Indian Panchatantra, through the Puritan primers of the 17th century, to the fairy tales of the Brothers Grimm, to the highly collectable Ladybird books of the 20th century, and up to modern classics and bestsellers such as the Harry Potter series. Illustrations have often been key components of children's stories, visualizing fantastic scenes and making them instantly recognizable. Original artwork from iconic illustrators such as Arthur Rackham, Walter Crane and John Tenniel is beautifully reproduced throughout.
Introduction -- First steps : oral traditions and pre-literacy -- Once upon a time, in a land far away -- Abecedarias and battledores -- The 'childe's first tutor' : the education of the young -- Small books for small people : the growth of publishing for the young -- Tales of tails : animal stories for children -- Innocence, experience and old-fashioned nonsense -- Fairies and frighteners : tempters, tearaways and cautionary tales -- Heroes in action : time-travel, detection and derring-do -- The war years and beyond -- Growing up fast : comics, TV and new media -- Records of a lost age : children's books as historical artefacts.
Includes bibliographical references (pages 264-265) and index.
Keywords: Children's books -- History; Children's literature -- History and criticism; Children -- Books and reading -- History; Illustrated children's books -- History; Printing -- History; Books and reading -- History; HISTORY / Civilization; LITERARY CRITICISM / Children's & Young Adult Literature